Broad Street, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
A busy Broad Street scene, showing business houses on both sides of the street, people going about their lives, and various modes of transportation. On the top left hand side is a building with the sign, W.L. JOHNSON & CO., next to a store with the sign, J.R. Bancroft & Co. DRY GOODS DEPARTMENT. Next, is COLLINS & CO. Carlisle Pharmacy. On the right hand side of the street is another business house, W.L. JOHNSON & CO. The image provides significant insight into the architecture of the business houses of the time. On the back: Published by Collins’ Carlisle Pharmacy 28, Broad Street, Barbados, MNTP £7
Landscape, black & white, 5 1/2 x 3 1/2 inches.
Keywords: Cities and Towns; Automobiles; Stores and shops; Business enterprises; Architectural elements; Buildings; Historic buildings; Transportation; J.R. Bancroft and Company Limited; W.L. Johnson and Company Limited; Collins and Company Carlisle Pharmacy